Crosstalk-free achromatic full Stokes imaging polarimetry metasurface enabled by polarization-dependent phase optimization - Zhang, Yaxin; Pu, Mingbo; Jin, Jinjin; Lu, Xinjian; Guo, Yinghui; Cai, Jixiang; Zhang, Fei; Ha, Yingli; He, Qiong; Xu, Mingfeng; Li, Xiong; Ma, Xiaoliang; et al. (Opto-Electronic Advances, 2022)
Imaging polarimetry is one of the most widely used analytical technologies for object detection and analysis. To date, most metasurface-based polarimetry techniques are severely limited by narrow operating bandwidths and inevitable crosstalk, leading to detrimental effects on imaging quality and measurement accuracy. Here, we propose a crosstalk-free broadband achromatic full Stokes imaging polarimeter consisting of polarization-sensitive dielectric metalenses, im-plemented by the principle of polarization-dependent phase optimization. Compared with the single-polarization optimiza-tion method, the average crosstalk has been reduced over three times under incident light with arbitrary polarization ran-ging from 9 μm to 12 μm, which guarantees the measurement of the polarization state more precisely. The experimental results indicate that the designed polarization-sensitive metalenses can effectively eliminate the chromatic aberration with polarization selectivity and negligible crosstalk. The measured average relative errors are 7.08％, 8.62％, 7.15％, and 7.59％ at 9.3, 9.6, 10.3, and 10.6 μm, respectively. Simultaneously, the broadband full polarization imaging capability of the device is also verified. This work is expected to have potential applications in wavefront detection, remote sensing, light-field imaging, and so forth.